Кто с тобой рядом: роман, рассказы / Гера Фотич - Фотич Гера (Любимый детектив, 2023)
Экземпляры: аб. ЦБ (20240527) / Инвентарный номер: 19878 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Ф 81 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=411.2)6-44